Effect of History of Deformation and Heat Treatment on Cold Drawing Process Parameters and Final Properties of AISI 302 Stainless Steel Wire - Maciej Rumiński (Archives of Metallurgy and Materials, 2023)
The paper focuses on the investigation of AISI 302 steel wire of different initial diameters, in solutionized condition. Three different drawing schedules were realized, starting from three different diameters, where two smaller-gauge wires were obtained by drawing of large-diameter wire and applying solution heat treatment to the product. However, the drawing schedules were carried out with almost the same total reduction and similar partial reductions. The measurement of drawing force was performed for each drawing pass, and the samples of wire were taken after each pass. The samples were then tested to obtain a set of mechanical and technological properties, as well as the distribution of Vickers hardness on wire cross section. Finally, the effect of different history of deformation and heat treatment on drawing process stability and final properties of drawn wires was discussed.